Strategies towards the synthesis of linear tetrapyrroles and the reactions of substituted pyrroles with sulfuryl chloride - Horan, Anne Marie (Trinity College (Dublin, Ireland). School of Chemistry, 2010)
The research undertaken in the present study describes the synthesis of bilins from easily obtainable starting materials using robust methods and the unusual reaction of SO2CI2 with tetrasubstituted pyrroles.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin.